Acquisition of Chinese characters: the effects of character properties and individual differences among second language learners - Kuo, Li-Jen; Kim, Tae-Jin; Yang, Xinyuan; Li, Huiwen; Liu, Yan; Wang, Haixia; Park, Jeong Hyun; Li, Ying (Frontiers in Psychology, 2015)
In light of the dramatic growth of Chinese learners worldwide and a need for cross-linguistic research on Chinese literacy development, this study drew upon theories of visual complexity effect (Su & Samuels, 2010) and dual-coding processing (Sadoski & Paivio, 2013) and investigated a) the effects of character properties (i.e., visual complexity and radical presence) on character acquisition and b) the relationship between individual learner differences in radical awareness and character acquisition. Participants included adolescent English-speaking beginning learners of Chinese in the U.S. Following Kuo et al. (2014), a novel character acquisition task was used to investigate the process of acquiring the meaning of new characters. Results showed that a) characters with radicals and with less visual complexity were easier to acquire than characters without radicals and with greater visual complexity; and b) individual differences in radical awareness were associated with the acquisition of all types of characters, but the association was more pronounced with the acquisition of characters with radicals. Theoretical and practical implications of the findings were discussed.